Development of Video-Based Learning Model Through “Seesaw” Application to Improve Process Skills Reviewed from the Motivation and Initial Understanding of Vocational High School Students - Prahestiningtyas, Tatag; Sulisworo, Dwi (Universitas Ahmad Dahlan, 2025)
Knowing how much learning has improved in students after using Physics learning media based on Video-Based Learning through the “Seesaw” application. This study employed a One-Group Pre-test Post-test Design. 34 SMK Bhakti Mulia Blora 10th-grade students served as the study's samples. The Simple Random Sampling technique was used to sample the sample members. Pre-experiment tests and questionnaires provided the data, which were then analyzed using paired t-tests. By using the